PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN AUDIO VISUAL TERHADAP KETERAMPILAN MENYIMAK KELAS VII-1 SMP PANCA BUDI MEDAN - br Tarigan, Dea Anggun Kinanti; Perangin-angin, Esra; Br Ginting, Sri Dinanta (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to determine the effect of audio-visual learning media on the listening skills of class VII-1 students of Panca Budi Middle School, Medan. The study focuses on Indonesian language learning, especially listening skills with the help of audio-visual media. The method used is an experiment with a pretest-posttest control group design. Data were obtained through listening skills tests before and after treatment, as well as observations during learning. The results of the descriptive analysis obtained an average pre-test score of 11.68 with a standard deviation of 2.450 and a standard error mean of 0.463, while the average post-test score was 16.04 with a standard deviation of 2.442 and a standard error mean of 0.461. The number of samples analyzed was 28 respondents. Thus, the results of the study show that the experimental group using audio-visual media obtained a significant increase in listening skills compared to the control group using conventional methods. Therefore, from the results of the descriptive analysis above, it can be concluded that the use of audio-visual media has a significant effect. Students also become more active and motivated during the learning process. Thus, audio-visual media is proven to be effective in improving the listening skills of junior high school students. In addition to these main findings, the study also uncovered several interesting facts. The increase in students' average listening skill score from 11.68 to 16.04 represents a jump of more than 37% after using audiovisual media. The stability of the standard deviation between the pre-test and post-test indicates that this improvement occurred evenly across all experimental groups. Furthermore, students became more active and motivated during the learning process, proving that audiovisual media is highly relevant and effective for a technology-savvy generation.